Functional mechanism and clinical implications of lncRNA NEAT1 in traumatic fractures and their correlation with delayed healing - Hua Meng; Zhaoyu Chen; Meng Han; Qianqian Cheng; Yanqi Shang; Hongqing Wang; Shenyi Lu (Journal of Orthopaedic Surgery and Research)
Abstract Background The clinical diagnosis of delayed fracture healing currently lacks molecular markers that exhibit both high sensitivity and robust dynamic detection capabilities. To evaluate the value of lncRNA NEAT1 for diagnosing delayed fracture healing and its potential mechanism of action. Methods 122 traumatic fractures patients were collected, including 61 normal fracture healing (NFH) patients and 61 delayed fracture healing (DFH) patients. LncRNA NEAT1 and miR-654-3p and osteoblast differentiation marker genes expression levels were examined using RT-qPCR. ROC curves and logistic analysis were used to assess lncRNA NEAT1 diagnostic value. CCK-8 method was used to detect the cell activity of osteogenic differentiated cells. Levels of apoptosis in osteogenic differentiated cells detected by flow cytometry. Relationship between lncRNA NEAT1 and miR-654-3p was detected by a dual luciferase reporter gene assay. Results The expression of lncRNA NEAT1 was upregulated in the serum of the DFH group. After osteoblast differentiation treatment, lncRNA NEAT1 level reduced while the level of miR-654-3p increased. A targeting relationship was found between lncRNA NEAT1 and miR-654-3p.and the expression levels were significantly negatively correlated. The lncRNA NEAT1 affected cell activity and apoptosis levels of osteogenic differentiated cells by regulating miR-654-3p. Conclusions lncRNA NEAT1 expression was up-regulated in DFH patient serum, and it has high diagnostic value for delayed fracture healing. lncRNA NEAT1 targeting miR-654-3p affected the activity and apoptosis of osteogenic differentiated cells.